(untitled) (Papeles, 2022)
Teaching second language learning strategies suggests that it is necessary to teach students the operation and benefit of learning strategies. However, it is not yet clear why low-achieving students do not progress significantly even when relevant aspects of their learning are improved. This study focused on a 55-year-old adult language learner with low performance in learning English. A qualitative research methodology was followed through a semi-structured interview, needs analysis, and observation. The results indicated that teaching strategies aimed at improving a specific skill do not show a significant improvement in their performance when using English. However, the student showed the deployment of a series of strategies that helped him manage the speech situation. In addition, it was found that motivation takes on a significant relevance not only in the use of new strategies, but also in language learning.